The Ethical Stakes of Collaborative Community-Based Social Science Research. (April 2018) - Glass, Ronald David; Morton, Jennifer M.; King, Joyce E.; Krueger-Henney, Patricia; Moses, Michele S.; Sabati, Sheeva; Richardson, Troy
This multivocal essay engages complex ethical issues raised in collaborative community-based research (CCBR). It critiques the fraught history and limiting conditions of current ethics codes and review processes, and engages persistent troubling questions about the ethicality of research practices and universities themselves. It cautions against positioning CCBR as a corrective that fully escapes these issues. The authors draw from a range of philosophic, African-centric, feminist, decolonial, Indigenous, and other critical theories to unsettle research ethics. Contributors point toward research ethics as a praxis of engagement with aggrieved communities in healing from and redressing historical trauma.